Profil Epidémiologique Des Lymphomes Malins NonHodgkinien Gastrique Au Maroc - Abdellah, Ben khali; Souad, Belamalem; Ali, Qyou; Ouazzani, Houria Chahed; Abdelmajid, Soulaymani (European Scientific Journal, ESJ, 2016)
Retrospective study was done on some cases having Malin Lymphoma Non-Hodgkin’s gastric recorded in Hepato-Gastroenterology department of University Hospital in Rabat during the period 2000 to 2010. The objective of this work is to identify primary and clinics Non Hodgkin lymphomas Malins of the stomach lymphosarcoma type. During the study periodwe registered 47 cases of Hodgkin’s Lymphoma Non Malin, an average of 4 Â± 0.59 cases / year. The majority of cases were from Kenitra-Rabat-Sale with 40% of cases. Males were the most affected with 55%. The chi-square test showed no significant difference between gender (Ï‡2 = 0.53, P> 0.05). 56 Â± 2.8 years. The average age of the patients was hospitalized with ends from 19 years to 85 years, a predominance of the age group [70-80 [with 24%. The majority of patients have a low socioeconomic level (95%). The most registered clinical signs are generally: Alteration of the general state (17%), fever (12%), anemia (10%), epigastric burn type and epigastric cramping in 8% for each of them. The location Antro - pyloric was the most frequent (54%), then the fundus location (18%) and diffuse forms in 9%.